Identificação da comunidade componente de helmintos, gastrointestinais hepáticos, pulmonares, cardíacos e renais de Otaria flavescens (Leão-marinho-do-sul), no litoral sul do Brasil - Pereira, Eliane Machado (2012)
This study verified helminth parasites infection in gastrointestinal tract, lungs, heart, and kidneys of southern sea lions, Otaria flavescens, from south coast of Rio Grande do Sul State, Brazil. Twenty-nine sea-lions were found dead on the beaches, whose carcasses had mild state of decomposition, were necropsied. The organs were collected during field necropsies for laboratory analyses were 24 small and large intestines, 24 livers including parenchyma and gall bladder, 29 stomachs, 24 hearts, and 24 pairs of kidneys. The organs were maintained frozen at -20°C until their processing. A sieve with 150µm mesh was used for screening the parasites. All content retained was analyzed under stereomicroscope. The helminthes were collected, counted, fixed in AFA, stained with carmine, and clarified in beechwood creosote. The small intestines were divided into three segments that were separately analyzed to record the distribution of helminthes by preference sites. Kolmorogov-Smirnov test was used to verify the type of data distribution. Comparison of mean abundance of infection between age classes was performed through Wilcoxon test at significant level of 0.05. Correlations between infection intensity, sex, total length of the individual, and length of small and large intestines were determined using Pearson s Correlation. Action® software version 1.1 was applied for statistical analyses. Among 29 specimens of O. flavescens 23 were males, three females, and three individuals whose sex could not be determined. The average length of the animals was 2.14±0.31m (1.58 to 2.64m) including 13 sub-adults and 16 adults. A total of 996 specimens of Contracaecum ogmorhini were recorded, especially in the stomach (10.34% of prevalence), 42,145 specimens of Corynosoma australe (100% of prevalence) and 512 of Bolbosoma turbinella (50% of prevalence) were found. Two species of trematodes were found: Stephanophrora uruguayense (Prev. 4.17%) and Ascocotyle (Phagicola) longa (Prev. 33.33% ), a estimated total of 1,988.202 specimens. Cestodes were found in only one of the hosts (4.16% of prevalence) which presented four scoleces. Macroscopically, liver, gall bladder, heart, lungs, and kidneys did not contain parasites. No significant correlation was observed between infection intensity, mean abundance, sex, total length of the host, or length of intestines. Infections levels were similar between sub-adults and adults sea lions. This is the first record of Diphyllobothrium sp., Bolbosoma turbinella, Contracaecum ogmorhini, Ascocotyle (Phagicola) longa, and Stephanoprora uruguayense in O. flavescens in Brazilian waters. As regards parasite fauna of O. flavescens, our data are different from those previously reported for specimens from Pacific coast of South America.